A Growth Mindset and Self-Affirmation Intervention to Reduce Violent and Risky Online Behaviors: The Moderating Role of Previous Victimization. Issue 7 (April 2023) - Calvete, Esther; Fernández-González, Liria; Orue, Izaskun
The Internet is the setting for several forms of violent and risky behavior among adolescents, such as cyberbullying, sexualized interactions with adults, sexting, and online dating violence. Often, these behaviors are responses to experiences of online victimization. This study examined the differential effects of a wise intervention (WI), combining growth mindset and self-affirmation strategies, on these behaviors for adolescents who had experienced victimization and those who had not. A sample of 1, 085 adolescents (54.3% girls; ages 11–18 years) were randomized into two intervention conditions (WI and an anti-stress control intervention). They completed measures of violent and risky behaviors at pretest and at 3- and 6-month follow-ups and measures of victimization at pretest. The results of multilevel analyses indicated that the WI was beneficial for adolescents without experiences of victimization at pretest, as they displayed smaller increases in online peer aggressions, sexualized interactions with adults, and sexting than the adolescents in the control condition. However, the WI was not beneficial for adolescents with experiences of victimization at pretest. Moreover, the adolescents under the anti-stress control condition displayed better outcome. These findings suggest that previous victimization experiences of adolescents should be considered to select an appropriate intervention.